Feminism of Khushal Khan Khattak - Tasal, Mohammad Qasim; Saqeb, Baryalay (Integrated Journal for Research in Arts and Humanities, 2023)
Khushal Khan was a well-known scientist and poet laureate, and his poetry and beliefs are quite close to those that are held now and relate to the present. This scholarly essay is about the feminism of khushal, while the first portion of express and dandify is concerned with feminism and the rights of women and girls. In the second half of Dastar Nama, a variety of khoshal's perspectives on the rights of women are examined, and the last section provides an allegory of the numerous sources.